The impact of online learning among UTAR FAS students - Peljeet Kaur Dhaliwal, Abtar Singh (2021)
This quantitative research aimed to identify the impact of online learning towards UTAR FAS students and to study the capabilities of UTAR FAS students on coping with online learning as it was important in identifying the responses given by UTAR students on the suitability of online learning as their preferred study mode. Based on past studies, there were several problem faced by students such as, lack of resources and proper communication platform in handling group assignments. This research was significant in identifying the student’s adaptability to online learning platform. Moving on, researcher used online survey to collect the respond to identify the impact of online learning among UTAR FAS students. The survey questions were divided into four variables which are usage of technology, flexibility of online learning, satisfaction of online learning and student’s workload. The researcher had successfully identified whether or not UTAR FAS students had perceived the ease of use and the usefulness in online learning. For instance, the finding had proved that all of the students agreed on the usage of technology. However, some students showed dissatisfaction on the flexibility, satisfaction, and student’s workload during online learning.